Зміцнення паперу документів: сучасні технології та нові матеріали - Затока, Л.П. (Рукописна та книжкова спадщина України, 2009)
Розглядаються основні напрями зміцнення ослабленої паперової основи документа. Надано інформацію про використання для консервації різноманітних клеєвих композицій – як традиційних, так і нових; про вимоги консерваційної науки щодо застосування для реставрації безпечних для документа речовин та матеріалів. Повідомляється про матеріали спеціального композиційного складу та призначення, які значно розширюють можливості фахівців щодо захисту та збереження раритетних документів. In this article there are discussed the basic methods of strengthening the weakened paper base of documents by using the different techniques like seizing, laminating with restoration paper and polymer film. It is provided the information about using for conservation the various seizing compositions, both the conventional and new ones. It is stated that strengthening of document paper with different chemical reagents and specific restoration papers must comply with the requirements of conservation art as to application for conservation of harmless substances and materials. It is also informed that for conservation objectives there are proposed the materials of specific composition and function which considerably extend the facilities to protect and preserve the rarity documents.